Voices from the Islands: A Qualitative Inquiry into Sustainable Tourism Practices in the Philippines - Loreño, Dustin Tarinque; Bari, Md Akramul (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study explores the dynamics of sustainable tourism development in the Philippines through a qualitative investigation of stakeholder perspectives in two leading ecotourism destinations: Palawan and Bohol. Despite the country’s growing emphasis on sustainability within national tourism policy, the actual practices and local interpretations of sustainable tourism remain understudied. Using a grounded theory approach, this study draws on twenty semi-structured interviews with local government officials, community leaders, tourism workers, and NGO representatives to uncover how sustainability is constructed and challenged in the Philippine context. The findings reveal five key themes: community empowerment, cultural and environmental stewardship, tensions with mass tourism, fragmented governance, and the mediating role of external actors. While local values such as “bayanihan” support sustainable practices, gaps in institutional coordination and unchecked commercial development hinder implementation. The study highlights the importance of integrating indigenous knowledge, ensuring local participation, and strengthening multi-level policy coherence. This paper contributes to the discourse on sustainable tourism in developing nations by emphasizing bottom-up approaches and culturally embedded models of tourism development. It offers practical implications for policymakers, destination managers, and development organizations seeking to align tourism growth with ecological protection and community well-being in the Philippines and other Southeast Asian contexts.